Occurrence of white spot syndrome (WSS) in a prawn farm at Cochin - Jose, Jasmine K; Manissery, Mary K (Indian Journal of Fisheries, 2011)
Occurrence of White Spot Syndrome (WSS) was notiped in farm reared Penaeusindicus H. Milne Edwards of size group 110- 150 mm at Munambam, Cochin inJanuary 1997. The affected prawns showed symptoms, similar to those reportedin P. monodon, such as sluggish movements, absence of feeding, escape reactions,reddish discolouration, white spots on cephalothorax and abdomen and loss of partof one or both the antennae. Histopathology of hindgut from the affected P. indicusrevealed the presence of inclusion bodies